An observational study of nurse staffing ratios and hospital readmission among children admitted for common conditions - Tubbs-Cooley, Heather L (BMJ Publishing Group, 2013)
BACKGROUND: Hospital patient-to-nurse staffing ratios are associated with quality outcomes in adult patient populations but little is known about how these factors affect paediatric care. We examined the relationship between staffing ratios and all-cause readmission (within 14 days, 15–30 days) among children admitted for common medical and surgical conditions. METHODS: We conducted an observational cross-sectional study of readmissions of children in 225 hospitals by linking nurse surveys, inpatient discharge data and information from the American Hospital Association Annual Survey. Registered Nurses (N=14 194) providing direct patient care in study hospitals (N=225) and children hospitalised for common conditions (N=90 459) were included. RESULTS: Each one patient increase in a hospital's average paediatric staffing ratio increased a medical child's odds of readmission within 15–30 days by a factor of 1.11, or by 11% (95% CI 1.02 to 1.20) and a surgical child's likelihood of readmission within 15–30 days by a factor of 1.48, or by 48% (95% CI 1.27 to 1.73). Children treated in hospitals with paediatric staffing ratios of 1 : 4 or less were significantly less likely to be readmitted within 15–30 days. There were no significant effects of nurse staffing ratios on readmissions within 14 days. DISCUSSION: Children with common conditions treated in hospitals in which nurses care for fewer patients each are significantly less likely to experience readmission between 15 and 30 days after discharge. Lower patient-to-nurse ratios hold promise for preventing unnecessary hospital readmissions for children through more effective predischarge monitoring of patient conditions, improved discharge preparation and enhanced quality improvement success.